Towards an indigenous Bible (in SASL) for deaf persons - S. Lombaard; J. A. Naudé (Acta Theologica)
The aim of this article is to give a proposal for an indigenous Bible in South African Sign Language (SASL) for Deaf persons. Due to deafness and the use of Sign Language, many Deaf people are often deprived of rights and privileges, simply because of communication problems and lack of understanding by the hearing community. SASL is a visual-gestural system with its own rules. Deaf people  focus on the visual and not on the auditive form of communication. Written language can therefore be regarded as a second language. Proposals are made for the conceptualising of the process and product of a signed Bible in electronic format.